PRIORITIZATION OF HUMAN CAPITAL DEVELOPMENT STRATEGY OF IMPROVING THE BANK PERFORMANCE - An Nisaa Noor Rachmawati; M. Syamsul Maarif; Anggraini Sukmawati (School of Business, IPB University (SB-IPB), 2020)
A human capital strategy is comprehensive planning about how the company achieves its vision and mission through human resources. This study aimed to formulate a prioritization strategy of human capital development for improving company performance used the Analytic Hierarchy Process (AHP). The hierarchy of AHP was arranged by considering five criteria that include an actor, company strategy, human capital management practice, company performance, the role of human capital division, and there were five alternative strategies. A questionnaire of AHP was arranged and presented to seven experts who were chosen from a multinational bank in Indonesia, they provided judgments based on a priority scale for each criterion. The result of the study showed that an actor who was prioritized was the human capital manager. The prioritization of the company strategy was the defender strategy. A human capital management practice that was prioritized was recruitment and selection. The prioritization of company performance was financial and the role of human capital division that was prioritized as a strategic partner. An alternative strategy that was prioritized to be implemented was building effective recruitment and selection systems. In conclusion, the company's performance can be improved through implementing effective recruitment and selection strategies and using validated psychometric instruments. Keywords: Analytic Hierarchy Process (AHP), balanced score card, compensation, performance management, recruitment and selection